1990
DOI: 10.3758/bf03205327
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure to conspecific and predator odors reduces fear reactions to these odors during subsequent prod-shock tests

Abstract: In Experiment 1, four groups ofmale rats were given a session as an intruder in either aggressive (i.e., alpha) or nonaggressive colonies of conspecifics and later received either a 2-h exposure to the odors of the alpha colonies or an exposure-control session with the odors of a nonalpha colony. Two additional groups of rats that had been attacked and defeated by alpha residents were later given a 12-h exposure session with alpha-colony odors or nonalpha-control odors. Twentyfour h after the colony-intruder s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
5
18
0
Order By: Relevance
“…This exploratory behaviour is similar to that observed for other mammals exposed to predator olfactory stimuli (Caine and Weldon 1989;McGregor et al 2002;. For example, rodents displayed similar odour assessment when presented with the scent of cat (Blanchard and Blanchard 1989;Williams et al 1990) The initial exploratory increase in f R by tammar wallabies generally decreased in the second minute. This is consistent with the hypothesis the initial reaction was investigative in nature.…”
Section: Discussionsupporting
confidence: 56%
“…This exploratory behaviour is similar to that observed for other mammals exposed to predator olfactory stimuli (Caine and Weldon 1989;McGregor et al 2002;. For example, rodents displayed similar odour assessment when presented with the scent of cat (Blanchard and Blanchard 1989;Williams et al 1990) The initial exploratory increase in f R by tammar wallabies generally decreased in the second minute. This is consistent with the hypothesis the initial reaction was investigative in nature.…”
Section: Discussionsupporting
confidence: 56%
“…More pertinent to the present study, it has been demonstrated that exposing rats to the odors of cats increased plasma levels of corticosterone (File et aI., 1993) and to the actual presence of a cat produced defensive fear responses and opioid-mediated analgesia (Lester & Fanselow, 1985;Williams & Barber, 1990;Williams & Groux, 1993;Williams, Rogers, et aL, 1990;Williams & Scott, 1989). As noted previously, opioid antagonists have been found to enhance memory Gallagher, Bostock, & King, 1985) and opioid agonists, such as morphine, to suppress memory (Spain & Newman, 1991).…”
Section: Discussionmentioning
confidence: 75%
“…Williams and his colleagues have shown that when rats are attacked and defeated by a dominant, or alpha male rat, learning and motivational deficits ensue that are accompanied by opioid-mediated analgesia (e.g., Hotsenpiller & Williams, 1996;Williams, 1989;Williams, Worland, & Smith, 1990). Of particular relevance to the current study, rats that have been exposed to a cat and/or cat odors, as a predator stressor, also display defensive fear responses and opioidmediated analgesia (Lester & Fanselow, 1985;Williams & Barber, 1990;Williams & Groux, 1993;Williams, Rogers, & Adler, 1990;Williams & Scott, 1989). In addition, File, Zangrossi, Sanders, and Mabbutt (1993) reported that when rats were exposed to the odors of cats intermittently for five daily sessions, they showed a significant increase in blood-plasma levels of corticosterone by the 3rd day.…”
mentioning
confidence: 91%
“…Previous research with rats [Williams et al, 1990a;Williams and Scott, 19891 led us to expect clear differences in responsiveness to these odors. Rearing, grooming, and digging behaviors were also recorded to provide some index of appetitive behaviors.…”
Section: Introductionmentioning
confidence: 93%